Politisasi Bahasa Melalui Eufemisme dalam Program Berita di Televisi - Hermaliza; Ermawati. S (GERAM: Gerakan Aktif Menulis, 2020)
This study discussed the politicization of language through euphemisms that conducted at the time of news broadcasts on television stations by noticing the background of the use of the euphemisms. Euphemism in the mass media is not merely aimed at replacing taboo words, but rather is ideological politics. The problem raised in this study was "How was the politicization of language through euphemisms in news programs on television in terms of its use?". The purpose of this study was to describe the form and function of politicizing the meaning of words through euphemisms in news programs contained on television. This research was a descriptive research. Data analysis was performed using content analysis and then explained in accordance with the research findings. Based on the results of the study, the authors found that politicized euphemisms in the TVone news program amounted to 30 euphemisms with several reasons why the euphemisms were chosen and used include: (1) to smooth out words so that other people are not offended, (2) to keep things secret, (3) for diplomacy or berororis, (4) to disguise meaning, (5) to avoid panic and fear, (6) to respect others.